Reestructuración comercial administrativa en la empresa Droguerías Rosas SAS. (2017)
The administrative commercial restructuring in the company Rosas SAS located in Bogotá D.C., is done in the first academical semester in 2017. A diagnosis is made with the objective of analyze the actual status of the company inside the sector and its behavior, this subject includes the application of tools as: PESTEL analysis, sector analysis, business self-diagnosis analysis by the Commerce Chamber of Bogotá D.C. and the SWOT matrix; It develops a market study with which analyzes the sector in which company operates and identifies critical factors in the market that affect the company, apply tools such as: market segmentation, survey, MPC matrix and business plan for the company; An administrative study, which proposes the strategic plan, organizational design, functions manuals and a process map are proposed. Lastly, is established the cost and expenses of each proffer in order to make the financial study, in which it is concluded that the project is feasible.